(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
The purpose of this research is to determine the effectiveness of the Duolingo application as a media for improving students’ English vocabulary mastery at seventh grade of SMP Swasta Muhammadiyah 19 Pematangsiantar. This research used a quantitative approach with a quasi-experimental design. The population of this research consisted of seventh-grade students, with two classes as samples: one experimental class (VII-3) and one control class (VII-1), each consisting of 24 students. The technique of collecting data was pre-test and post-test, and the data were analyzed using SPSS version 27.0. The result of the research showed that Tcount (3.212) > Ttable (1.684) at the significance level α = 0.05 with degrees of freedom (df) = 46. This indicates that H0 is rejected and Ha is accepted. Based on the findings, the post-test score was higher than the pre-test score. It can be concluded that there was a significant improvement in students’ vocabulary mastery after the treatment using the Duolingo application. Therefore, the researcher concludes that the Duolingo application is effective in enhancing students’ English vocabulary mastery. Duolingo offers gamified learning, interactive practice, and user-friendly features, making vocabulary learning more engaging and accessible. Students found it enjoyable and motivating, which supports vocabulary retention and development in an effective way